TRANSFORMATIONAL LEADERSHIP IN ISLAMIC EDUCATION MANAGEMENT IN THE DIGITAL AGE: CHALLENGES AND IMPLEMENTATION STRATEGIES - Muhammad Fazis; Jamilus Jamilus; Ferdino Wedi Sanjaya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The rapid advancement of digital technology has significantly transformed the management of educational institutions, including those in Islamic education, creating the need for leadership capable of managing organizational change while preserving Islamic values. This study aims to analyze the role of transformational leadership in Islamic education management in the digital era by identifying its major challenges, implementation strategies, and implications for sustainable educational governance. The study employed a qualitative descriptive approach using library research. Data were collected from books, peer-reviewed journal articles, and relevant policy documents related to transformational leadership, Islamic education management, and digital transformation, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that transformational leadership plays a strategic role in strengthening organizational vision, enhancing digital competencies, promoting innovation, fostering collaborative organizational cultures, and integrating Islamic values into educational governance. The analysis also identifies limited digital literacy, inadequate technological infrastructure, organizational resistance to change, and digital governance as the primary challenges affecting successful digital transformation. The study contributes to the development of Islamic education management by proposing a comprehensive conceptual framework that integrates transformational leadership, digital transformation, and Islamic values as a foundation for sustainable educational governance.